World Maritime Day : shipping safety 100 years after the Titanic - Sam, Bateman (2012)
World Maritime Day on Thursday 27 September focuses attention on shipping safety. Much has been achieved over the years but shipping accidents continue to occur and there are no grounds for complacency.